1993
DOI: 10.1183/09031936.93.06060877
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of fluticasone propionate, 1 mg daily, with beclomethasone dipropionate, 2 mg daily, in the treatment of severe asthma. International Study Group

Abstract: We wanted to compare the efficacy and safety of fluticasone propionate, a new topically active inhaled corticosteroid, to that of high dose beclomethasone dipropionate, in severe adult asthma. Patients currently receiving between 1.5-2.0 mg.day-1 of an inhaled corticosteroid were treated for six weeks in a double-blind, randomized, parallel group study with 1 mg.day-1 fluticasone propionate (n = 82), or 2 mg.day-1 beclomethasone dipropionate (n = 72). Mean morning peak expiratory flow rates (PEFR) increased fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Fluticasone propionate is a new, topically active, synthetic glucocorticosteroid which has been shown in both adults and children to be at least twice as clinically effective as beclomethasone dipropionate 10–13 . Fluticasone propionate has the added advantage over other currently available inhaled corticosteroids of having less than 1% oral bioavailability; hence there will be few or no systemic effects from the swallowed portion of the inhaled dose 9 , 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluticasone propionate is a new, topically active, synthetic glucocorticosteroid which has been shown in both adults and children to be at least twice as clinically effective as beclomethasone dipropionate 10–13 . Fluticasone propionate has the added advantage over other currently available inhaled corticosteroids of having less than 1% oral bioavailability; hence there will be few or no systemic effects from the swallowed portion of the inhaled dose 9 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies in healthy adult volunteers have demonstrated that fluticasone propionate has a higher local potency than existing inhaled corticosteroids, 8 and that it undergoes virtually complete first‐pass degradation by the liver to inactive metabolites 9 . In clinical studies in adults, fluticasone propionate has been shown to be at least twice as effective as beclomethasone dipropionate in improving lung function but with the same or a better safety profile 10–12 . In children, fluticasone propionate has also been compared with beclomethasone dipropionate 13 and shown to have greater efficacy with no significant adverse events or reduction in serum cortisols.…”
mentioning
confidence: 99%
“…Clinical asthma severity was rated as mild, moderate or severe using the integrated severity score described in the Australian Asthma Management Guidelines [6], which closely approximate the National Heart, Lungs and Blood Institute Guidelines [7]. Appropriate inhaler use and compliance was assessed in the Asthma Management Service [8].…”
mentioning
confidence: 99%